2023
DOI: 10.1186/s10020-023-00643-4
|View full text |Cite
|
Sign up to set email alerts
|

m6A methyltransferase METTL3 programs CD4+ T-cell activation and effector T-cell differentiation in systemic lupus erythematosus

Abstract: Background Systemic lupus erythematosus (SLE) is an autoimmune disorder in which excessive CD4+ T-cell activation and imbalanced effector T-cell differentiation play critical roles. Recent studies have implied a potential association between posttranscriptional N6-methyladenosine (m6A) modification and CD4+ T-cell-mediated humoral immunity. However, how this biological process contributes to lupus is not well understood. In this work, we investigated the role of the m6A methyltransferase like 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…7,8 Recent studies on MMP9 and ischemic stroke has provided valuable insights into the complex interplay between MMP9 and various aspects of ischemic stroke, including blood brain barrier (BBB) dysfunction, cognitive impairment, therapeutic targets and pathophysiological changes. [9][10][11] The SNPs characteristics of MMP9 and Ischemic stroke were considered robust instrumental variables (Supplementary Table S2). Figures 10A and C illustrate the individual genetic variations' causal effects on SLE.…”
Section: Mmp9 Is Causally Associated With Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Recent studies on MMP9 and ischemic stroke has provided valuable insights into the complex interplay between MMP9 and various aspects of ischemic stroke, including blood brain barrier (BBB) dysfunction, cognitive impairment, therapeutic targets and pathophysiological changes. [9][10][11] The SNPs characteristics of MMP9 and Ischemic stroke were considered robust instrumental variables (Supplementary Table S2). Figures 10A and C illustrate the individual genetic variations' causal effects on SLE.…”
Section: Mmp9 Is Causally Associated With Ischemic Strokementioning
confidence: 99%
“…[5][6][7][8] METTL3 plays a key role in regulating the activation and differentiation of CD4 + T cells, and its downregulation in SLE patients may impact T cell-mediated immune responses. 9 Conversely, the upregulation of circGARS, acting as a sponge for miR-19a, affects the expression of the m6A reader YTHDF2 and A20, consequently modulating the NF-κB pathway, potentially exacerbating SLE pathology. 10 Additionally, the differential expression of m6A-modified long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) in SLE patients suggests their potential roles in the disease, possibly serving as new therapeutic targets for SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that inhibiting METTL3 facilitates the activation of CD4 + T cells while suppressing the differentiation of effector T cells, particularly Treg cells, by reducing the expression of Foxp3 in a m6A-dependent manner [ 247 ]. Inhibition of METTL3 reduces m6A methylation levels, promotes cell apoptosis, hinders effector T cell differentiation, and inhibits allogeneic CD4 + T cell responses [ 24 ].…”
Section: Classification Of Rna Methylationmentioning
confidence: 99%